Estimating UK perennial energy crop supply using farm‐scale models with spatially disaggregated data. Issue 2 (1st November 2013) - Alexander, Peter; Moran, Dominic; Smith, Pete; Hastings, Astley; Wang, Shifeng; Sünnenberg, Gilla; Lovett, Andrew; Tallis, Matthew J.; Casella, Eric; Taylor, Gail; Finch, Jon; Cisowska, Iwona
Abstract To achieve the UK Government's aim of expansion in the growth of perennial energy crops requires farmers to select these crops in preference to conventional rotations. Existing studies estimating the total potential resource have either only simplistically considered the farmer decision‐making and opportunity costs, for example using an estimate of annual land rental charge; or have not considered spatial variability, for example using representative farm types. This paper attempts to apply a farm‐scale modelling approach with spatially specific data to improve understanding of potential perennial energy crop supply. The model main inputs are yield maps for the perennial energy crops, Miscanthus and willow grown as short‐rotation coppice (SRC), and regional yields for conventional crops. These are used to configure location specific farm‐scale models, which optimize for profit maximization with risk aversion. Areas that are unsuitable or unavailable for energy crops, due to environmental or social factors, are constrained from selection. The results are maps of economic supply, assuming a homogenous farm‐gate price, allowing supply cost curves for the UK market to be derived. The results show a high degree of regional variation in supply, with different patterns for each energy crop. Using estimates of yields under climate change scenarios suggests that Miscanthus supply may increase under future climates while the opposite effect is suggested for SRC willow. The results suggest that SRC willow is only likely to able to supply a small proportion of the anticipated perennial energy crop target, without increases in market prices. Miscanthus appears to have greater scope for supply, and its dominance may be amplified over time by the effects of climate change. Finally, the relationship to the demand side of the market is discussed, and work is proposed to investigate the factors impacting how the market as a whole may develop.